1987
DOI: 10.3354/meps038251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixation on particle retention by microflagellates: underestimation of grazing rates

Abstract: The uptake of fluorescent particles by protists and filter-feeding metazoa is being used increasingly by microbial ecologists to study feeding behavior and measure grazing rates. Recent studies of microflagellate uptake of these inert particles have yielded inconsistent results. In particular. grazing rates determined from fluorescent particle uptake are often less than rates measured using other techniques. These low uptake rates have been attributed to osmotrophy, food quality or size selection, rapid egesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 19 publications
2
70
1
Order By: Relevance
“…Recently, some scientists indicated that protozoan zooplankton preferred living (Landry et al, 1991) or motile (Gonzalez et al, 1993) bacteria to non-living fixed ones. Moreover, fixation often caused flagellates to egest food vacuole contents (Sieracki et al, 1987). These informations suggest that it is possible that estimation of HNF grazing rates on bacteria obtained by heat-killed FLB method in the present study are underestimated.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, some scientists indicated that protozoan zooplankton preferred living (Landry et al, 1991) or motile (Gonzalez et al, 1993) bacteria to non-living fixed ones. Moreover, fixation often caused flagellates to egest food vacuole contents (Sieracki et al, 1987). These informations suggest that it is possible that estimation of HNF grazing rates on bacteria obtained by heat-killed FLB method in the present study are underestimated.…”
Section: Discussionmentioning
confidence: 54%
“…Although it has been et al. 1985), this typical pattern of batch culture has been achieved in several studies (Sieracki and Sieburth 1985;Tranvik and Hofle 1987) and indicates the absence of significant bacterivore populations.…”
Section: Resultsmentioning
confidence: 99%
“…For each grazing estimate, five subsamples of 5 ml were transferred from each of the cultures of the bacterivory experiment to test tubes containing FLB, adjusted to correspond to -8% of the total number of free bacteria in the test tube. Subsamples were fixed after 0, 5, 10, 15, and 20 min by adding an equal volume of a 4% glutaraldehyde and 4% acrolein solution (Sieracki et al 1987), prepared with 0.2-pm-filtered water from Barber Pond.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ abundance of strains MED479 and MED134 was checked. At time 0 and after 40 min of incubation, aliquots for DAPI-stained microbial counts and FISH analysis were taken as before, with the exception that fixation was carried out with an equal volume of diluted fixative to reduce cell egestion (Sieracki et al, 1987) and that the final glutaraldehyde concentration was 2%. The incubation time (40 min) was chosen based on a previous time series that showed a plateau in the number of ingested bacteria at 45 min (Unrein et al, 2007).…”
Section: Grazing Experimentsmentioning
confidence: 99%